Biomass and carbon distribution on Imperata cylindrica grasslands - Syahrinudin Syahrinudin; Manfred Denich; Mathias Becker; Wahjuni Hartati; Paul LG Vlek (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Syahrinudin, Denich M, Becker M, Hartati W, Vleg PLG. 2020. Biomass and carbon distribution on Imperata cylindrica grasslands. Biodiversitas 21: 74-79. Invasive plants can alter the diversity and composition of ecological communities leading to ecosystem change both function and biodiversity issues. Imperata cylindrica is an invasive grass thrives on wide range of soil fertility and climatic condition forming a vast grassland area of this species. Conversion of such lands into agriculture and plantation is costly and high capital demanding. This work was devoted to investigate CO2 mitigation potential of the conversion I. cylindrica grassland to plantations in Sumatra and East Kalimantan, Indonesia. Stratified sampling technique was applied for the determination of biomass and carbon stock of the system studied. Results show that I. cylindrica grassland stored only a relatively small amount of biomass C (5.9-7.6 mg ha-1) implying that conversion into a more C-rich tree-based system would be promising tool to enhance C sequestration. Soil C content at both study sites decreased significantly with depth from the top 15 cm to the 3-m depth and was considerably higher in East Kalimantan than in Sumatra. Provided similar land-use history, the differences in soil C are likely to be related to the level prior to the invasion. Roots of I. cylindrica extended to a maximum depth of only 180 cm, but most of these roots being confined to the topsoil, little organic material is deposited in deeper layers. Despite the dense mat of rhizomes, the extent of C stored in the topsoils was modest. As sequestration is of global concern, the conversion of this grassland into systems with higher biomass accumulation and deeper root penetration is required.